2013
DOI: 10.1371/journal.pone.0060890
|View full text |Cite
|
Sign up to set email alerts
|

E-Selectin Mediated Adhesion and Migration of Endothelial Colony Forming Cells Is Enhanced by SDF-1α/CXCR4

Abstract: ObjectiveEndothelial-colony forming cells (ECFCs) can be readily expanded from human umbilical cord blood and can facilitate repair of endothelial injury. E-selectin and SDF-1α are produced following endothelial injury and can regulate endothelial progenitor homing. Mechanisms of vascular repair specific to the mode of injury have not been well described in homogenous cell populations such as ECFCs and are needed for development of more effective vascular repair strategies.Methods and ResultsLipopolysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…18 After isolation, ECFCs were cultured in EBM-2 Q8 medium supplemented with SingleQuot supplements (Lonza, Basel, Switzerland), 10% (v/v) fetal bovine serum, and 1% (v/v) 10,000 U/mL penicillin/ 10,000 mg/mL streptomycin/25 mg/mL amphotericin, as described. 18 Cells were seeded onto tissue culture plates precoated with gelatin at 37 C, 5% CO 2 , in a humidified incubator. Before injection, cells (passage 3 to 4) were detached using trypsin-EDTA, washed twice in 1Â phosphate-buffered saline (PBS), and resuspended in 1Â PBS at a final concentration of 10 7 cells/mL.…”
Section: Isolation and Culture Of Ecfcsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 After isolation, ECFCs were cultured in EBM-2 Q8 medium supplemented with SingleQuot supplements (Lonza, Basel, Switzerland), 10% (v/v) fetal bovine serum, and 1% (v/v) 10,000 U/mL penicillin/ 10,000 mg/mL streptomycin/25 mg/mL amphotericin, as described. 18 Cells were seeded onto tissue culture plates precoated with gelatin at 37 C, 5% CO 2 , in a humidified incubator. Before injection, cells (passage 3 to 4) were detached using trypsin-EDTA, washed twice in 1Â phosphate-buffered saline (PBS), and resuspended in 1Â PBS at a final concentration of 10 7 cells/mL.…”
Section: Isolation and Culture Of Ecfcsmentioning
confidence: 99%
“…By flow cytometry, ECFCs (passage 4, n Z 4) expressed high levels of CD31 (82.5% AE 5.7% positive) and vascular endothelial growth factor receptor 2 (88.5% AE 2.4%), but lacked significant CD45 (0.5% AE 0.2%), CD14 (0.9% AE 0.3%), and CD133 (0.8% AE 0.3%) expression, consistent with our previous report. 18 The effects of human ECFCs were studied in NOD-SCID mice subjected to 30 minutes of bilateral kidney I/R. Compared with sham-operated on mice, I/R increased plasma creatinine levels at 24 and 72 hours after reperfusion (Figure 1 ½F1 ½F1 , A and B).…”
Section: Effects Of Ecfcs On I/r-induced Kidney Injurymentioning
confidence: 99%
“…We recently demonstrated that endothelial cells produced increased levels of stromal cellederived factor (SDF)-1a injury compared with hypoxic or radiationassociated injury. The migration of ECFCs, likewise, was mediated via distinct mechanisms with increased expression of E-selectin ligands on ECFCs induced by SDF-1a binding to CXCR4 after LPS-induced injury of endothelial cells [43]. The extent to which specific angiogenic cells or EPCs are mobilized into the peripheral circulation may provide a useful prognostic biomarker, with specific subsets of circulating CD34-positive angiogenic cells correlating with cardiovascular risk and the number of endothelial cluster-forming cells Q 5 correlating with Framingham risk scores [44,45].…”
Section: Endothelial-like Vascular Progenitor Cellsmentioning
confidence: 99%
“…Herein, certain matrix effectors, cytokines, and chemokines may be delivered to shift the balance towards promoting EPC homing to the target tissue. 73,81 Direct and indirect interactions between such factors and components of the ECM dictate how they are presented to and subsequently stimulate the surrounding cells. 67 Therefore, control over the spatiotemporal presentation of factors is crucial for the intended biological effect to be achieved.…”
Section: Biomaterials Delivery Of Soluble Factors For Manipulating Endmentioning
confidence: 99%
“…31,46 EPC mobilization and homing is a multi-step process involving detachment from their steady state bone marrow (BM) niches, entry into circulation, rolling along vessel endothelium, transmigration, and adhesion to denuded extracellular matrix (ECM) where they may participate in neovessel formation. 45,73 All of these processes are under the tight regulation of chemokines and their receptors. However, these mechanisms are often interrupted in pathological conditions partly due to matrix modulation and an imbalance in factor presentation at the tissue level.…”
Section: Introductionmentioning
confidence: 99%